A importância das modificações de estilo de vida para a gestão da COVID-19 - Ibatova, Aygul Z. (Revista EntreLinguas, 2021)
Months after the coronavirus disease (COVID-19) outbreak in 2019, which has spread quickly as a pandemic in different parts of the world, affecting all sectors in state agencies and non-governmental organizations (NGOs), while the violation of recommendations for safety and self-care has grown into the most recent global crisis. As the given disease has caused vast closures and disruptions in education, politics, economics, etc., it has led to massive death tolls in the history of humankind. To avoid the rising prevalence rate of this virus, all individuals have to make some changes in their lifestyles, based on new scientific findings, even if these attitudes, ways of life, values, or world views are so far from what are recognized for centuries and managed in accordance with social world trends.